2005
DOI: 10.1111/j.1742-4801.2005.00083.x
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐effective faster wound healing with a sustained silver‐releasing foam dressing in delayed healing leg ulcers – a health‐economic analysis

Abstract: The aim of this analysis was to examine the cost-effectiveness of Contreet Foam (A) in comparison with three other commonly used venous leg ulcer treatment protocols: Aquacel Ag (B), Actisorb Silver (C) and Iodoflex (D). A health-economic analysis reflecting the UK treatment practice and cost structure was performed. The analysis was set up to assess the cost of relative wound area reduction over a 4-week treatment period. The model was validated by a UK expert panel consisting of four wound care specialists. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 23 publications
0
30
0
Order By: Relevance
“…Aquacel Ag ® was also evaluated for the treatment of chronic wounds,29,30,38,39 which have an increased bacterial burden that can impair healing, albeit without all the clinical signs of infection. Silver can provide a mechanism for controlling the wound bacterial burden.…”
Section: In Vivo Efficacymentioning
confidence: 99%
“…Aquacel Ag ® was also evaluated for the treatment of chronic wounds,29,30,38,39 which have an increased bacterial burden that can impair healing, albeit without all the clinical signs of infection. Silver can provide a mechanism for controlling the wound bacterial burden.…”
Section: In Vivo Efficacymentioning
confidence: 99%
“…There was no significant difference between the groups in wound healing at 12 weeks, but the silver dressings were associated with much higher costs [59]. However, a comparison study found a silver-releasing foam dressing to be more cost-effective than other silver-containing products, including an ionic silver hydrofiber dressing and a silverimpregnated activated charcoal dressing [60]. Other concerns related to use of silver dressings are a greater frequency and number of visits and longer total duration of wound care, which may increase costs [61].…”
Section: Topical Application For Ulcersmentioning
confidence: 97%
“…With the advent of antibiotics circa World War II, the use of silver for many of these functions declined, only to be revived in the 1960s by Moyer and Fox, as described below [reviewed in 3]. Several studies failed to show benefit in overall wound healing Some studies favor use of silver-releasing foam dressing [55,60,62], whereas others show higher cost [59,61] Current data do not support routine use of silver for this application…”
Section: Historymentioning
confidence: 99%
“…In a cost effectiveness analysis (supported by a grant from the manufacturers of Contreet Foam) using indirect comparisons between Contreet Foam, Aquacel Ag, Actisorb Silver and iodoflex (antimicrobial with gauze) in patients with delayed healing leg ulcers, the cost per percentage reduction in wound area over 4 weeks was assessed 19. The authors stated that they used this analysis because no studies were available following patients to complete healing (which the authors indicated occurs in 50–75% of ulcers within 1 year and 71–87% by 2 years).…”
Section: Clinical Evidencementioning
confidence: 99%